The Effect of Osthole on Transient Receptor Potential Channels: A Possible Alternative Therapy for Atopic Dermatitis - Kordulewska NK; Król-Grzymała A (Dove Medical Press, 2024)
Natalia Karolina Kordulewska, Angelika Król-Grzymała Department of Biochemistry, Faculty of Biology and Biotechnology, University of Warmia and Mazury, Olsztyn, 10-719, PolandCorrespondence: Natalia Karolina Kordulewska, Oczapowskiego 1A, Olsztyn, 10-719, Poland, Tel +48 89 523 37 63, Fax +48 89 535 20 15, Email natalia.smulska@uwm.edu.plIntroduction: Chronic recurrent skin inflammation and severe itching in patients with atopic dermatitis (AD) significantly impair their quality of life. The H4 histamine receptor plays a key role in histamine-induced itching. During the skin inflammation associated with AD, pro-inflammatory mediators (interleukins, cytokines) are released from neurons. Ultimately, a cascade of reactions leads to the activation and sensitization of transient receptor potential channels (TRP), which exacerbate the inflammation and itching associated with AD. Osthole (OST) is a natural coumarin with a proven versatile pharmacological effect: anti-cancer, anti-inflammatory and immunomodulatory. However, the molecular mechanism of OST in relieving inflammation in histamine-mediated itching is not yet clear.Purpose: In the studies presented, the possible effect of the OST action on the inhibition of the gene expression of the histamine H4 receptor and the key genes of the TRP channels as well as on the concentration of proinflammatory interleukins was analyzed.Methods: Inflammation was induced in a 3D skin model and a keratinocyte cell line Normal Human Epidermal Keratinocytes (NHEK) identical to that of AD, and then OST was administered at various doses. The concentrations of IL-4/-13 were determined by ELISA. RNA was isolated from the 3D skin cells and the NHEK cell line, and the qPCR method was used to determine the expression of: IL-4α, H4R, TRPV1, TRPV4, TRPM8 analyzed.Results: The study showed that OST significantly reduced the secretion of IL-4/-13 in a keratinocyte cell line and in a 3D skin model. In addition, OST was found to significantly decrease the gene expression of IL-4α, H4R, TRPV1, TRPV4 and increase TRPM8 in both the NHEK cell line and the organotypic 3D skin model.Conclusion: The data obtained provide the first in vitro evidence of itch relief following the application of OST to atopic skin. Research on the use of OST as an active component of emollients in the treatment of AD should be continued in the future.Keywords: pro-inflammatory cytokines, keratinocytes, clobetasol propionate, CP, TRPV channels, 3D skin